ANALISIS NERACA AIR PASCATAMBANG PADA TAILING STORAGE FACILITY - M Anshari Akbar; Ginting Kusuma; Rudy Benggolo; Abie Badhurahman (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Tailings Storage Facility (TSF) has environmental impacts and risks arising from the tailings storage. Water balance is an important component in TSF management. In this study, the water balance was analyzed to determine the method of handling TSF during mine closure, to reduce the risk of environmental pollution. Analysis of the rainfall and potential evaporation parameters was used to calculate the water discharge that must be managed in mine closure. The method of selecting daily maximum rainfall data was used to analyze the need for TSF facilities. Meanwhile, for mine closure TSF filling, scenarios for extreme climate conditions were made for the rainfall and potential evaporation parameters which were then analyzed to determine the water balance. Based on the daily data analysis, the maximum amount of water discharge that must be managed at the TSF was 1.511 m3/s. Meanwhile, for TSF charging, it was found that the fastest charging scenario took 31.8 months and for the longest charging it took 110.4 months. To determine the method of handling TSF during mine closure, the results of water balance analysis for several scenarios of climatic conditions resulted in the minimum thickness of the water column ranging from 6 - 8 m. Based on the analysis of several scenarios of climatic conditions, the mine closure method for handling TSF was water cover.